2021
DOI: 10.1002/adfm.202103920
|View full text |Cite
|
Sign up to set email alerts
|

4D Printing of Multi‐Responsive Membrane for Accelerated In Vivo Bone Healing Via Remote Regulation of Stem Cell Fate

Abstract: Dynamic regulation of substrate micro‐structures is an effective strategy to control stem cell fate in tissue engineering. Translating this into in vivo tissue repair in a clinical setting remains challenging, which requires precise temporal control of multi‐scale structural features. Using 4D printing technique, a multi‐responsive bilayer morphing membrane consisting of a shape memory polymer (SMP) layer and a hydrogel layer, is fabricated. The SMP layer is featured with responsive surface micro‐structures, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 44 publications
0
55
0
Order By: Relevance
“…Current studies have demonstrated their ability in shape-morphing with time for dynamic culture, which can encourage more studies of the 4D printed bone tissues and implants. [220,248,249] In addition to the biodegradation and biocompatibility of the 4D bone scaffolds, more deep studies in terms of in vitro differentiation and in vivo implantation should be performed in the future. Considering the in vivo implantation, mechanical properties such as compression strength and fatigue strength are another consideration for the choice of 4D bone materials.…”
Section: Bone Regenerationmentioning
confidence: 99%
See 3 more Smart Citations
“…Current studies have demonstrated their ability in shape-morphing with time for dynamic culture, which can encourage more studies of the 4D printed bone tissues and implants. [220,248,249] In addition to the biodegradation and biocompatibility of the 4D bone scaffolds, more deep studies in terms of in vitro differentiation and in vivo implantation should be performed in the future. Considering the in vivo implantation, mechanical properties such as compression strength and fatigue strength are another consideration for the choice of 4D bone materials.…”
Section: Bone Regenerationmentioning
confidence: 99%
“…synthesized a dual stimulus‐responsive SMP that can achieve the swelling‐induced macroscopic morphing and heat‐induced microscopic morphing. [ 248 ] The dynamic cell culturing surface, the static micropillar surface, and the static flat surface were printed using a DLP printer ( Figure A). The study results showed the continuous spreading of the cytoskeleton on the dynamic surface.…”
Section: Biomedical Applications Of 4d Printingmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the inherent selfrepair ability of bone, the gold standard for defect treatment is still autologous bone transplantation (Zhang et al, 2017;Annamalai et al, 2019;Li et al, 2020). With the progression of tissue engineering, biomimetic bone scaffolds can guide tissue regeneration with assembled stem cells (Zhao et al, 2019;Swanson et al, 2021;You et al, 2021). Therefore, they have considered a cost-effective and osteoinductive strategy to replace autologous bone grafts (Cui et al, 2019).…”
Section: Introductionmentioning
confidence: 99%